Visualising the surface water system: an environmental justice-led approach - Bowman, Bryony M.; Hunt, Dexter V. L.; Rogers, Chris D. F. (Frontiers in Water, 2024)
It is becoming increasingly apparent that the management, protection and utilization of water requires a place-based and systems perspective to enable complexity to be visualized and assessed. Understanding the complexity of relationships across this system enables an appreciation of impacts across social, environmental and economic perspectives. This paper explores the surface water system through an environmental justice lens, identifying key pathways which both support and inhibit movement toward environmental justice using system mapping techniques. While socio-economic systems, and the impact these have on the surface water system, are demonstrably important, these externalities are difficult to predict into the future, potentially impacting the system in a variety of ways. To address this uncertainty, future scenarios, based on the archetypes generated by the Global Scenarios Group, were developed at the surface water system scale. Exploring the impact of diverse future scenarios on the surface water system through an environmental justice lens enabled the characterization of leverage points and the formation of a conceptual model. Analysis of the conceptual model determined the existence of three feedback loops centred around circular generation, cost and value recovery, and urban development. This paper presents an approach for the development of visualizations and a conceptual model to enable evidence-based societal and environmental impacts to be analyzed through a justice lens. In doing so this creates a platform to enable cross-sectoral and cross-societal exploration of drivers and impacts using a common method of communication.